Effects of a 3-Month Combined Training Program (Endurance, Strength, and Flexibility) on Physical Fitness Levels and Students’ Attitudes Toward Exercise - Sarkabood, Younes (Mental Health and Lifestyle Journal, 2026)
Promoting and sustaining physical fitness can be effectively achieved through regular complementary exercise routines. This study aimed to evaluate the impact of a 3-month combined training program, implemented over an academic semester, on selected physical fitness components and students’ attitudes toward physical activity and training modalities. A total of 263 students (mean age: 20 ± 2.8 years) participated and were assessed pre- and post-intervention, with results compared to a control group that did not perform regular physical activity. Data were analyzed using paired t-tests. The results revealed significant improvements (P < 0.05) in cardiovascular endurance, muscular strength, and endurance of the abdominal and shoulder girdle muscles following the intervention. However, no significant changes were observed in the explosive strength of the calf muscles (P > 0.05). Two training approaches were employed: (1) combined aerobic, strength, and flexibility exercises; and (2) the same protocol supplemented with rhythmic sports music. At the semester's end, students’ attitudes were assessed via a questionnaire covering five domains: sports performance, program content, exercise attractiveness, exercise variety, and appropriateness of exercise intensity. Significant positive differences (P < 0.05) were found in sports performance, program content, variety, and intensity appropriateness, whereas no significant difference was noted in exercise attractiveness (P > 0.05). In conclusion, the combined training program positively enhanced participants’ physical fitness levels, supporting its recommendation for improving fitness among young women. Additionally, students exhibited particularly favorable attitudes toward aerobic exercises incorporating sports music, especially regarding program content.